Development of a medicinal chemistry e-module using a team-based learning strategyDevelopment of a medicinal chemistry e-module using a team-based learning strategy - Ida Adhayanti; Sesilia Rante Pakadang (JINoP (Jurnal Inovasi Pembelajaran), 2025)
Many pharmacy students consider Medicinal Chemistry a complex subject due to its abstract concepts and highly technical content. This study aimed to develop a digital e-module tailored to the characteristics and needs of vocational pharmacy students and to implement it using a Team-Based Learning (TBL) strategy to enhance engagement and motivation. The development process adopted the Rowntree model, consisting of planning, writing, and evaluation phases. Subject matter and media experts designed and validated six thematic submodules. The readability score was computed using the Gunning Fog Index, while additional evaluations were performed through usability testing (face-to-face) and field implementation. Expert and student assessments indicated that this e-module was rated “Very Good” in terms of content, design, and visual aspects. The mean readability score of 9.8 suggested appropriate textual complexity for the undergraduate level. By engaging students further through TBL, motivation, participation, and comprehension increased, as demonstrated by perception scores across four learning domains. Both the structured e-modules and collaborative learning worked in unison to transform what is traditionally perceived as a hard-to-teach subject into an interactive and enjoyable experience. Future studies should include multimedia enhancements and investigate broader implementation across other complex pharmaceutical courses.